STUDY OF THE INTERCONNECTION BETWEEN INTRAPERSONAL CONFLICT, TEMPERAMENTAL AND PERSONAL MEASURES AMONG STUDENTS - Kukso, Polina; Kiryukhina, Evgenia; Kukso, Olga; Mochalov, Sergey (Revista Inclusiones, 2020)
The article deals with the problem of intrapersonal conflict among students in the period of their professional development. Students are in the period of youth, which is critical in the psychological development periodization system. The aim of this research is to reveal connection between intrapersonal conflict and some of the temperamental measures among students, on the one hand, and between intrapersonal conflict and the temperamental measures depending on sex, on the other hand. Three groups of students with a different type of intrapersonal conflict were distinguished. Based on the data obtained, some types of intrapersonal conflict reflecting peculiarities of intrapersonal antagonism of the young people studying in higher education institutions were singled out. A comparative analysis of temperamental and personal measures of students from these groups was conducted.